Restrictive diffusion and hydrodesulfurization reaction of dibenzothiophenes over NiMo/SBA‐15 catalysts. Issue 5 (26th January 2022) - Wang, Bo; Chen, Zhentao; Jiang, Tao; Yu, Jiahuan; Yang, Haoxuan; Duan, Aijun; Xu, Chunming
Abstract: Macromolecular organosulfur compounds encountered resistance when diffusing in catalyst pore channels during the hydrotreating process. Quantitative insights into the effects of the catalyst pore size and the reactant molecule size on the diffusivities can guide the optimization of the catalyst structures. Herein, a heavy oil macromolecular dibenzothiophene compound, 2, 8‐di‐(4‐pentyl phenyl)dibenzothiophene (2, 8‐DPPDBT), was synthesized. Three NiMo‐supported SBA‐15 based catalysts with different pore sizes, but similar active phase dispersions were controllably fabricated. The reaction network of 2, 8‐DPPDBT HDS was proposed. The diffusion behaviors of 2, 8‐DPPDBT, along with 2, 8‐dimethyl dibenzothiophene (2, 8‐DMDBT) and dibenzothiophene (DBT) in three SBA‐15 pore channels, were systematically investigated through the reaction kinetic method. A restrictive factor, F ( λ ), was correlated by F ( λ ) = (1 −  λ ) 8.5 to determine the relationship between the effective diffusivity and the ratio of the molecule‐to‐pore size ( λ ). This empirical correlation provided sound theoretical guidance on the design of highly efficient heavy oil hydrodesulfurization catalysts.